Biopsy of breast cancer metastases: patient characteristics and survival. Issue 1 (December 2017) - Shachar, Shlomit; Mashiach, Tanya; Fried, Georgeta; Drumea, Karen; Shafran, Noa; Muss, Hyman; Bar-Sela, Gil
Abstract Background Discordance in hormone receptors (HR) and human epidermal growth factor receptor 2 (HER2) status between primary tumors and metastatic sites for breast cancer is well established. However, it is uncertain which patient-related factors lead to biopsy when metastases are suspected and whether having a biopsy impacts survival. Methods The medical charts of metastatic breast cancer (MBC) patients diagnosed January 2000-August 2014 were retrospectively reviewed. A biopsy was defined as a procedure where tissue was obtained and assessed for both HR and HER2. Both bivariate and multivariate analyses were performed to assess patient characteristics related to biopsy and whether having a biopsy was associated with improved survival. Results Of 409 patients suspected of having MBC, 165 (40%) had a biopsy, and 34% of these had discordant HR or HER2 status when compared to the initial diagnosis. In multivariate analysis, having a biopsy was associated with: recurrence in years 2010–2014, disease-free interval of > =3 years, stage 0-IIA at presentation, suspected locoregional recurrence, being HR+/HER2-, or missing HR/HER2 at diagnosis. A similar multivariate analysis revealed that having a biopsy was associated with improved survival (HR = 0.67, p = 0.002). The association of biopsy and improved survival was noted in specific subgroups: patients with missing HR and HER2 data at initial diagnosis (p = 0.001), those without metastases in liver, lung or brain (p = 0.001), and being younger than 70 years old at recurrence (p < 0.001). Conclusions Specific clinical factors were associated with biopsy at the time of suspected recurrence. Having a biopsy was associated with reduced mortality.